2011
DOI: 10.1080/00288330.2011.562143
|View full text |Cite
|
Sign up to set email alerts
|

Land use influences stream nitrate uptake in the Lake Taupo catchment

Abstract: We quantified nitrate (NO 3 ( ) uptake during summer for 11 streams draining into oligotrophic Lake Taupo. Nitrate uptake lengths (S w ) ranged from 258 to 12035 m, uptake velocities (V f ) ranged from 0.2 to 6.8 m/day and removal efficiencies (P r ) ranged from 1% to 59%. Nitrate uptake velocities and areal uptake rates were, respectively, 9-and 26-fold higher for streams in pasture and pine forest land use than in native vegetation. However, average NO 3 ( export from these streams was also 8-fold higher. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Hence a minimum concentration of 80% of saturated concentration is required by the Resource Management Act (1991). In most studies, concentrations of DO in mature forests were above this concentration (Collier and Bowman 2003;Collier and Halliday 2000;Matheson et al 2011;Pruden et al 1990). An exception of 72% was recorded in a forested Northland stream by Baillie et al (2005), which the authors attributed to the warmer thermal regimes in this region.…”
Section: Mature Forest Phase: Canopy Closure To Forest Maturitymentioning
confidence: 99%
See 2 more Smart Citations
“…Hence a minimum concentration of 80% of saturated concentration is required by the Resource Management Act (1991). In most studies, concentrations of DO in mature forests were above this concentration (Collier and Bowman 2003;Collier and Halliday 2000;Matheson et al 2011;Pruden et al 1990). An exception of 72% was recorded in a forested Northland stream by Baillie et al (2005), which the authors attributed to the warmer thermal regimes in this region.…”
Section: Mature Forest Phase: Canopy Closure To Forest Maturitymentioning
confidence: 99%
“…A preliminary study by Fish (1968) found very low levels of Cu (often below detection (Collier and Bowman 2003;Cooper et al 1987;Fahey and Stansfield 2006;Friberg et al 1997;Harding and Winterbourn 1995;Macaskill et al 1997;Matheson et al 2011;Parkyn et al 2006;Thompson et al 2009;Thompson and Townsend 2004b;Townsend et al 1997;Young et al 2005). The wider range of NO 3 -N/ NO x -N concentrations compared with TN is influenced by studies that measured that measured concentrations of NO 3 -N at the high end of the range and either did not measure TN or measured TN at a lower sampling intensity than NO 3 -N. Death et al 2003;Friberg and Winterbourn 1997;Harding and Winterbourn 1995;Parkyn et al 2006;Quinn et al 1997;Quinn et al 2004;Shearer and Young 2011;Stark and Maxted 2007;Townsend et al 1997.…”
Section: Mature Forest Phase: Canopy Closure To Forest Maturitymentioning
confidence: 99%
See 1 more Smart Citation
“…); (iii) periphytic biofilms can reduce summer stream nitrate loads up to 59%, particularly in shallower, faster‐flowing streams with higher water column P availability (Matheson et al . ); and (iv) vegetated drains have some capacity for nutrient retention (Nguyen & Sukias ). However, in streams with high nutrient concentrations, in‐stream plants may not be able to reduce nutrient loads (O'Brien et al .…”
Section: Riparian Sciencementioning
confidence: 99%
“…Bankside experimental systems demonstrated declines in instream nutrient uptake by periphyton with increased levels of shading (Quinn et al 1997;Matheson et al 2012) and provided confirmation of the summer-time nutrient uptake potential of watercress (Sukias & McKergow 2010). In situ short-term nutrient addition experiments have shown the following: (i) low-nutrient uptake rates in low-nutrient tussock streams (Simon et al 2005); (ii) nutrient uptake is correlated with periphyton chlorophyll a (Niyogi et al 2004); (iii) periphytic biofilms can reduce summer stream nitrate loads up to 59%, particularly in shallower, faster-flowing streams with higher water column P availability (Matheson et al 2011); and (iv) vegetated drains have some capacity for nutrient retention (Nguyen & Sukias 2002). However, in streams with high nutrient concentrations, in-stream plants may not be McColl (1978), Smith (1992), Hicks (1992), Williamson et al (1996), Davies-Colley (1997) (Tables S1-S3) able to reduce nutrient loads (O'Brien et al 2014).…”
Section: Wa Ter Qua Litymentioning
confidence: 99%